2011
DOI: 10.1002/hyp.8336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urbanization on stream hydrology and water quality: the Florida Gulf Coast

Abstract: At the global scale, the population density of coastal areas is nearly three times that of inland areas, and consequently, land development represents a threat to coastal ecosystems. It is critical to understand how increasing urbanization affects coastal watersheds. To that end, the objective of this study was to examine the influence of urban development on stream water quality and hydrology in a coastal setting, a scenario that has received less attention than other physiographic regions. Stream hydrologic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 40 publications
5
24
0
7
Order By: Relevance
“…This indicates that these wetlands had become increasingly surface water driven as opposed to groundwater driven as they would naturally occur. Similar effects of LULC on stream hydrology have been repeatedly demonstrated elsewhere (Blann et al, 2009;Hardison et al, 2009;Nagy et al, 2011). Many studies have also found changes in base and peak flow levels because of changing land use (Paul and Meyer, 2001); however, our results did not detect a correlation between watershed run-off (CN and Q) and water table height.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…This indicates that these wetlands had become increasingly surface water driven as opposed to groundwater driven as they would naturally occur. Similar effects of LULC on stream hydrology have been repeatedly demonstrated elsewhere (Blann et al, 2009;Hardison et al, 2009;Nagy et al, 2011). Many studies have also found changes in base and peak flow levels because of changing land use (Paul and Meyer, 2001); however, our results did not detect a correlation between watershed run-off (CN and Q) and water table height.…”
supporting
confidence: 63%
“…Urbanization also modifies landscape drainage by increasing impervious surface area that has been shown to increase run-off, reduce water quality and alter stream morphology (Paul and Meyer, 2001;Boggs and Sun, 2011). A general understanding of the effects of land use and land cover (LULC) on streams has emerged (Walsh et al, 2005;Blann et al, 2009;Nagy et al, 2011); however, less is known about upstream headwater wetlands. Headwater wetlands are a critical zone in the drainage network representing the interface between terrestrial and aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wetland vegetation in major creeks and marshes includes Nyssa sylvatica biflora (swamp tupelo), Taxodium distichum (bald cypress), and Sabal palmetto (cabbage palm; Anderson & Lockaby, ). Common tree species in the watershed include Pinus clausa (sand pine), Pinus elliottii (slash pine), Quercus virginiana (live oak), and Cyrilla racemiflora (titi; Chelsea Nagy et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The development of urban environments leads to an increase of nutrients concentration and fecal coliforms due to the discharge of domestic effluents [4]. This contamination promotes modifications in the physical-chemical characteristics of the water, and in turn, the quality of the aquatic environment [5]. The addition of nutrients promotes ecosystem-level problems, such as algal blooms, biochemical oxygen demand increase and hypoxia [6].…”
Section: Introductionmentioning
confidence: 99%